Contribution of Parenting Patterns and Social Environment Through the Phenomenon of Gadget Addiction to Juvenile Delinquency in the Rural-Urban Area of Malang City, Indonesia - Wahyuni, Sri; Sri Redjeki, Endang; Listyaningrum, R. Anggia; Avrilianda, Decky (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
The reason of this researchto: 1) analyze the impact of child rearing fashion on adolescent wrongdoing in rural-urban ranges of Malang City, 2) analyze the impact of the social environment on adolescent wrongdoing in rural-urban zones of Malang City, 3)analyze the impact of child rearing fashion and social environment through the wonder of contraption compulsion to adolescent wrongdoing in rural-urban ranges of Malang City. The inquire about strategy utilized is quantitative way examination. The populace in this ponder were guardians who had adolescent children in rural-urban ranges of Malang City, totaling 9157 individuals, particularly the guardians chosen were moms. Assurance of the number of tests utilizing the slovin edge of mistake equation of 10% with a add up to test adjusted up to 99 individuals. Inspecting method by implies of Basic Irregular Testing. The child rearing and social environment factors somewhat impact the adolescent wrongdoing variable, since it features a critical esteem less than 0.05 and tcount>ttable. At that point at the same time and impacted by interceding factors, to be specific the phenomenon of contraption habit to adolescent misconduct features a positive impact, since the esteem of Fcount>Ftable and a critical esteem is less than 0.05